Trichoderma spp. no biocontrole de Macrophomina phaseolina e no crescimento de feijoeiro - Sarzi, Janaina Silva (2019)
Macrophomina phaseolina is one of the main pathogens of common bean, causing the disease known as charcoal rot, it is disseminated through seeds and able to attack many species of plants. It is a difficult pathogen to control, since it produces resistance structures that allow it to remain viable in the soil for a long period of time. Therefore, the use of practices such as crop rotation present low control efficiency, however, using antagonist organisms may be an effective measure in handling this pathogen, while also aiding in plant growth promotion. Thus, the aim of this work has been to evaluate Trichoderma spp. action in the biocontrol of M. phaseolina and in common bean plant growth, as well as identifying composts produced by Trichoderma spp. with potential fungicide. In order to do so, two Trichoderma spp. isolates were used, one of commercial formulation, and one of common bean rhizospheric soil, as well as two pathogenic isolates of M. phaseolina. The antagonistic action of Trichoderma spp. over M. phaseolina was evaluated through pairing of cultures and volatile metabolites, the most adequate means of liquid culture for cultivating the antagonist as well as growth and activity in in vitro biocontrol of M. Phaseolina have been determined subsequently. Culture filtrates and living organisms of Trichoderma spp. isolates were used in the treatment of seeds for evaluating growth promotion. In order to evaluate disease control, application of filtrate culture has been made, along with spores of living organisms of the antagonist in seeds as well as inoculation of the pathogen by substrate or direct contact with the seed. Lastly, identification of composts with potential fungicide produced by the antagonist was carried out through means of spectrophotometer analysis and gas chromatography. Trichoderma spp. isolates have been efficient in controlling M. phaseolina mycelial growth both in pairing of cultures as well as through volatile metabolites. Both Trichoderma spp. isolates have produced chitinase and only T. harzianum has produced β-1,3-glucanase. Trichoderma spp. isolates cultivated in liquid environment have produced hydroxyl and fatty acids described in literature with potential fungicide and induction of defense response in plants. The application of Trichoderma spp. alive or filtered, through seed treatment, has been capable of controlling charcoal rot disease from the stalk, caused by M. phaseolina in common bean. T. virens has a positive effect over root growth in common bean.